A abordagem minimalista da verdade de Paul Horwich - Rodrigues, Yuri de Lima (2020)
The purpose of this dissertationis to present and defend the minimalism about truth, a theory developed over the last thirty years by the British philosopher Paul Horwich (1947-) and which is still at the center of the debate in the field of truth theory.According to this theory, the best way available to understand the general concept of truth is through the use of the equivalence scheme -a logical form according to which a proposition P is true if and only if P. The purpose of this theory is to reduce the conceptual resources required to understand truth, which is explained in this theory employing a general concept, that is, a concept formed from absolutely all current or possible uses of the truth. The methodology to be used to defend this theory consists of two steps. First, I willpresent other ways of understanding the general concept of truth and criticize them for problems such as (1) lack of conceptual clarity, (2) circularity, (3) theoretical limitation, and (4) unnecessary complexity. Second, Iwill argue that minimalism doesnot have these problems, which makes it the best theory in comparative terms. Problems (1) and (2) will be identified in conventional philosophical ways. But, to defend the existence of problems (3) and (4) in the hypotheses considered, I will assume two minimalist hypotheses: the hypothesis of unformulatable propositions and the hypothesis of explanatory sufficiency of the equivalence scheme. According to the first hypothesis, unformulatable propositions may exist and a general theory of truth should allow us to understand what it would be like if we could apply truth to them. According to the second hypothesis, each instance of the equivalence scheme can be understood as a priori in such a way that each of them does not need justification and can be considered satisfactory to understand truth. This research will present three results: (1) the understanding that truth is a logical property, (2) an absolute view of truth, and (3) an example of the success of a late Wittgensteinian way of doing philosophy. The defense that truth is a logical property will be due to the fact that during this research we concluded that truth must be (1) understood a priori (2) through a logical form that (3) theoretically has a maximum level of generality. As a conclusion of this research, minimalism is reaffirmed, but under a different perspective.